2022
DOI: 10.1002/vrc2.270
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐guided saphenous and sciatic nerve block as part of multimodal pain management in a goat undergoing tibial fracture repair

Abstract: A 6-week-old goat was presented for surgical repair of a Salter Harris type 1 fracture of the right tibia. The goat was premedicated with butorphanol 0.2 mg/kg and midazolam 0.2 mg/kg intramuscularly, followed by induction of anaesthesia with ketamine 1 mg/kg and propofol 3.2 mg/kg intravenously. Anaesthesia was maintained with isoflurane in an oxygen air mix. An ultrasound-guided saphenous and sciatic nerve block was performed using 0.1 ml/kg/nerve of ropivacaine 0.75%. Except for a slight gradual decrease in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…This locoregional anaesthetic technique has been previously published in dogs and in a 6-week-old goat to localise the nerves of interest. 7,16 However, to the authors' knowledge, this is the only clinical report using this approach in an adult goat undergoing trochlear sulcoplasty for lateral patellar luxation with the preservation of motor function of the limb to promote quicker recovery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This locoregional anaesthetic technique has been previously published in dogs and in a 6-week-old goat to localise the nerves of interest. 7,16 However, to the authors' knowledge, this is the only clinical report using this approach in an adult goat undergoing trochlear sulcoplasty for lateral patellar luxation with the preservation of motor function of the limb to promote quicker recovery.…”
Section: Discussionmentioning
confidence: 99%
“…26 Different studies in goats showed the efficacy of ropivacaine when local anaesthetic techniques were performed. 16,27 Therefore, it was the best choice for the authors on this pet-owned goat.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations